PENGARUH DANA PIHAK KETIGA (DPK) DAN RETURN ON ASSET (ROA) TERHADAP JUMLAH PENYALURAN KREDIT PADA BANK PEMERINTAHAN (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Saputra, Nur Syawala; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine how the effect Third Party Fund ( TPF ) and Return On Asset (ROA) against lending at Bank Government (BUMN). In this study using secondary data obtained from Indonsia Stock Exchange (IDX) period 2008 – 2016. Samples were taken by purposive sampling and samples that met the selection criteria. Sample used as many as 4 bangking companies.The analytical method used is the Multiple Linear Regression Analysis . Tests conducted on the hypothesis and the reliability of the data (classical assumption) using significant rate of 5 %.From the results of tests performed on the simultaneous study showed that the level of mortgage Third Party Funds (TPF) and Return On Asset by F test significant influence is 0.000. The results partially by t test , to see the test results significant independent variable on the analysis of multiple factors affecting the loan portfolio in the Government -owned banks in Indonesia , it can be seen that the Third Party Funds variables are variables that significantly influence against lending at Bank government (BUMN) 0.000. By looking at the results of the coefficient of the independent variable return on asset (ROA) is a variable that does not significantly influence lending at Bank government (BUMN). Keywords : TPF ( third party funds ), Return On Asset (ROA) and Lending